2012
DOI: 10.1007/s00068-012-0212-z
|View full text |Cite
|
Sign up to set email alerts
|

Serial lactate and admission SOFA scores in trauma: an analysis of predictive value in 724 patients with and without traumatic brain injury

Abstract: Objective Arterial lactate, base excess (BE), lactate clearance, and Sequential Organ Failure Assessment (SOFA) score have been shown to correlate with outcome in severely injured patients. The goal of the present study was to separately assess their predictive value in patients suffering from traumatic brain injury (TBI) as opposed to patients suffering from injuries not related to the brain. Materials and methods A total of 724 adult trauma patients with an Injury Severity Score (ISS) C 16 were grouped into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 39 publications
(40 reference statements)
1
36
0
Order By: Relevance
“… Regnier, 2012 [ 48 ] 281 Prospective 2 h, 4 h 2 h Early normalization of lactate independent predictor of survival 32. Dubendorfer, 2013 [ 49 ] 724 Retrospective Variable Variable In patients without traumatic brain injury, decrease in lactate impaired in nonsurvivors 33. Odom, 2013 [ 50 ] 623 Retrospective ≥4 6 h 6 h Lower decrease in lactate at 6 h independently predictive of increased risk of death 34.…”
Section: Resultsmentioning
confidence: 99%
“… Regnier, 2012 [ 48 ] 281 Prospective 2 h, 4 h 2 h Early normalization of lactate independent predictor of survival 32. Dubendorfer, 2013 [ 49 ] 724 Retrospective Variable Variable In patients without traumatic brain injury, decrease in lactate impaired in nonsurvivors 33. Odom, 2013 [ 50 ] 623 Retrospective ≥4 6 h 6 h Lower decrease in lactate at 6 h independently predictive of increased risk of death 34.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in line with recently published findings that suggest that blood lactate concentration upon ED arrival is predictive of mortality, independent of SOFA score. Patients with contemporaneous blood lactate and SOFA score measurements at admission were enrolled in limited prospective cohort studies [27, 29, 30]. Our study was conducted in a large mixed cohort of NF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous adult studies have demonstrated the effects of initial base excess and blood lactate on predicted mortality in brain trauma patients. 14,15 Severe TBI profoundly disturbs cerebral acid-base homeostasis, and brain tissue acidosis can cause further neural death. 16 Acidosis can cause secondary insult to the brain by exacerbation of cerebral edema and further increases the risk of mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%